2009
DOI: 10.1080/14992020902971349
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nonlinear frequency compression: Clinical outcomes

Abstract: This study evaluated prototype multichannel nonlinear frequency compression (NFC) signal processing on listeners with high-frequency hearing loss. This signal processor applies NFC above a cut-off frequency. The participants were hearing-impaired adults (13) and children (11) with sloping, high-frequency hearing loss. Multiple outcome measures were repeated using a modified withdrawal design. These included speech sound detection, speech recognition, and self-reported preference measures. Group level results p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
255
10
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(293 citation statements)
references
References 45 publications
26
255
10
2
Order By: Relevance
“…These results comply with studies conducted in subjects with and without ZMC, where audibility and recognition of monosyllables, consonants, plural and/or fricatives in silence showed better results with the use of techniques for lowering the frequencies 14,15,17,18,20 . It is also highlighted that the n of the present research was established by means of a sampling calculation, based in international articles, which, mostly have smaller samples 14,15,17,20 than the one from the study that is presented.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These results comply with studies conducted in subjects with and without ZMC, where audibility and recognition of monosyllables, consonants, plural and/or fricatives in silence showed better results with the use of techniques for lowering the frequencies 14,15,17,18,20 . It is also highlighted that the n of the present research was established by means of a sampling calculation, based in international articles, which, mostly have smaller samples 14,15,17,20 than the one from the study that is presented.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, considering the fact that the improvement is already seen in half of the subjects immediately, it is believed that the percentage of seniors benefiting from the use of CNLF in this study may, after a period of acclimatization, be even greater, as already observed in previous studies 14,33,34 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…These results concur with the researched literature (9,22,23,24,25) . In one study, the use of a frequency transposition algorithm in hearing impaired individuals with presence of dead regions in the cochlea, from 1.5 kHz, was efficient in the identification of the phoneme / ∫ / and, in general, there was no Identification of the other phonemes of the English language.…”
Section: Discussionsupporting
confidence: 83%
“…Also, selected measurement tools may not have been sensitive enough to the subtle effects of NFC or LFT HAs, or not representative enough of real life. Other researchers used more analytical tasks, such as consonant recognition or /s/ detection [34][35][36][37]. We chose to use ecological outcome measures closer to real-life experience that are also considered clinical standard tests.…”
Section: Discussionmentioning
confidence: 99%